Computing resilience of process plants under Na-Tech events: Methodology and application to sesmic loading scenarios. (March 2020) - Caputo, Antonio C.; Kalemi, Bledar; Paolacci, Fabrizio; Corritore, Daniele
Highlights: A novel procedure for resilience calculation of process plants under Na-Tech events is proposed. The methodology is strongly based on actual physical structure of the process and PERT/CPM technique, and it provides a direct estimation of capacity loss and the recovery function. The model can be applied both in deterministic and probabilistic manner and is generalizable to any kind of Na-Tech hazard. The applicability of the methodology has been shown in computating the seismic resilience of a nitric acid plant. Abstract: Resilience is a performance measure representing both the capability of a system to survive a disruptive event and the ability of rapidly restoring the operational status recovering the initial capacity. However, literature is lacking about methods allowing to compute resilience of process plants from a technical point of view. In fact, in the process industry the scarce literature about resilience mainly focused on organizational issues. In order to contribute to fill this gap a methodology has been developed to estimate resilience in case of Na-Tech events for process plants. The methodology provides a direct estimation of capacity loss after the disruptive event, and the time trend of recovery as well as the related economic loss. The model can be applied both in deterministic and probabilistic manner and is generalizable to any kind of Na-Tech hazard. However, in this paper specific reference is made to seismic hazard. In order to show the capabilities of the methodology a case study is also described referring to a Nitric Acid plant. Results show the predictive capabilities of this approach and the usefulness as a decision making tool for facility planners and emergency managers in the process industry.